Pengaruh Karakteristik Wirausaha, Modal Usaha Dan Pemasaran Online Terhadap Pengembangan Umkm Kuliner Di Kecamatan Natar - Tri Lestira Putri Warganegara; Lana Bilbirri (Journal Of Business, Finance, and Economics (JBFE), 2022)
This study aims to see the influence of entrepreneurial characteristics, business capital and online marketing on the development of Culinary, Micro, Small and Medium Enterprises in Natar District. The population in this study are Culinary, Micro, Small and Medium Enterprisessin Natar District. The sampling method in this study was non-probability sampling using the Lemeshow formula so that a sample of 74 respondents was obtained. The research method used is quantitative research. The type of data used is primary data. Multiple regression analysis and correlation were performed using SPSS software version 26. The results showed that if the t test stated that entrepreneurial characteristics and venture capital had a positive and significant effect on business development, online marketing had no effect on business development. While the F test states that the characteristics of entrepreneurship, business capital and online marketing jointly influence the development of Culinary Micro, Small and Medium Enterprises in Natar District.